Robot solution: um kit para o estímulo de competências do pensamento computacional - Marinho, Deyse dos Santos (2023)
The transformations that affect man throughout his history show his cognitive development through the construction of artifacts. Realizing man's dominance over the elements of nature and the gradual improvement of these processes, shows how much construction techniques impact technologies, and consequently, affect man. In this intrinsic relationship between man and nature, personal and social development can be seen. However, this development does not occur homogeneously and generates plural societies with discrepancies in technological knowledge. This scenario, defined by irregular technological progress, commands for urgent solutions based on educational processes, in order to propose cognitive and social development obeying the dynamism of technological aspects. Harari (2018) said that man does not understand digital technologies in their entirety, hence the question: How to appropriate these technological resources? Based on the maker mentality, in the vision of Seymour Papert and Dale Dougherty, seeks to rescue the builder man, and thus, activate primitive instincts driven by curiosity and creativity. Maker Culture promotes teaching in a fun, challenging and enjoyable way. As a teaching resource, Educational Robotics is used, which offers creative and differentiated activities encouraging innovation. The construction of robotic projects is a strategy that allows the inclusion of the Programming Language and the pillars of Computational Thinking, from the perspective of Jeannette Wing and Christian Brackmann. In this way, different aspects are developed in parallel in the cognitive, social, psychomotor, affective fields and, mainly, the development of skills and competencies specific to Computational Thinking. Therefore, this research follows the guidelines provided by the BNCC and the PCN for High School, the target audience to be reached, with a view to achieving an emancipatory and necessary education in the current technological society. As a product resulting from this practice, a robotic kit was developed, which presents the creation of its parts adaptable to different materials and seeks to reach a diverse audience. The teaching guide was created based on the thoughts of Zabala (2014), which helps learning by reformulating its contents – Conceptual, Procedural and Attitudinal – which are in line with what is proposed by the Educational Robotics and Maker Culture approaches.